Analysis of the Role of Perceived Social Support on Depressive Symptoms in Adolescents Mediated by Self-Compassion - mulia sari, silvia ananda; Siswanto, Siswanto (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
One of the common mental health problems experienced by teenagers is depression. If not handled properly, depression in adolescents can cause various significant negative impacts on their psychological well-being and social functions. This research aims to examine and test the role of perceived social support towards depression symptoms in adolescents, with self-compassion as a mediator variable. The hypothesis proposed in this study is that self-compassion mediates the relationship between perceived social support and symptoms of depression in adolescents. The population in this study consists of students from a private senior high schools in Semarang City, with a total of participants of 102 people (N= 102) and an age range between 15 to 18 years old. The data collection instrument used is in the form of a psychological scale, namely the Depression Symptoms Scale- Center for Epidemiologic Studies Depression Scale Revised (CESD-R), Self-Compassion Scale- Self-Compassion Scale (SCS), Perceived Social Support - The Multidimensional Scale of Perceived Social Support (MSPPS). Data analysis is carried out using mediation analysis through the help of IBM SPSS version 25, using macro PROCESS model 4 (Hayes). The results of the analysis show that self-compassion mediates the relationship between perceived social support and depressive symptoms with an effect value of -0,462. (Bootstrap 95% Cl: -0,596 to -0,334). This finding indicates that perceived social support not only has a direct effect on depression symptoms, but also indirectly through increased self-compassion in adolescents.Salah satu masalah kesehatan mental yang umum dialami oleh remaja adalah depresi. Apabila tidak ditangani secara tepat, depresi pada remaja dapat menimbulkan berbagai dampak negatif yang signifikan terhadap kesejahteraan psikologis maupun fungsi sosialnya. Penelitian ini bertujuan untuk mengkaji dan menguji peran perceived social support terhadap gejala depresi pada remaja, dengan self-compassion sebagai variabel mediator. Hipotesis yang diajukan dalam penelitian ini adalah bahwa self-compassion memediasi hubungan antara perceived social support dan gejala depresi pada remaja. Populasi dalam penelitian ini terdiri atas siswa dari salah satu SMA swasta di Kota Semarang, dengan jumlah partisipan sebanyak 102 orang (N= 102) dan rentang usia antara 15 hingga 18 tahun. Instrumen pengumpulan data yang digunakan berupa skala psikologis, yaitu skala Skala Gejala Depresi- Center for Epidemiologic Studies Depression Scale Revised (CESD-R), Skala Self-Compassion- Self-Compassion Scale (SCS), Perceived Social Support - The Multidimensional Scale of Perceived Social Support (MSPPS). Analisis data dilakukan dengan menggunakan analisis mediasi melalui bantuan perangkat lunak IBM SPSS versi 25, dengan menggunakan macro PROCESS model 4 (Hayes). Hasil analisis menunjukkan bahwa self-compassion memediasi hubungan antara perceived social support dan gejala depresi dengan nilai efek sebesar -0,462. (Bootstrap 95% Cl: -0,596 hingga -0,334). Temuan ini mengindikasi bahwa perceived social support tidak hanya berpengaruh secara langsung terhadap gejala depresi, tetapi juga secara tidak langsung melalui peningkatan self-compassion pada remaja.